Integration of Climate Change into the Senior Secondary School Agricultural Science Curriculum in Nigeria - Ikeh, Michael E.i; Ifeanyieze, Florence O.; Ugwuoke, Cajethan Uche (Atmospheric and Climate Sciences, 2014)
The study was carried out to identify content areas of climate change for integration into the senior secondary school agricultural science curriculum in countries such as Nigeria. Two research questions were developed and answered by the study while two null hypotheses were formulated and tested. Descriptive survey research design was adopted for the study. The population for the study was 441 while the sample was 249. A 34-item structured questionnaire was developed for data collection. The questionnaire items were face-validated by five experts while Cronbach alpha method was used to determine the internal consistency of the items. The copies of the questionnaire were administered to the respondents with the help of two research assistants. Weighted mean was used to answer the research questions while t-test statistic was used to test the null hypotheses at 0.05 level of significance and 240 degrees of freedom. The findings of the study revealed that four clusters with 23 items were required for integration in the curriculum while 11 materials were identified to help teach the content areas. It was also found that there was no significant (p > 0.05) difference in the mean responses of Lecturers and extension agents on each item in the content areas of climate change and materials for teaching them. The study recommended among others that the clusters and 23 items with the materials identified by the study should be integrated into the agricultural science curriculum for teaching in secondary schools, especially in Nigeria.
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Integration of Climate Change into the Senior Secondary School Agricultural Science Curriculum in Nigeria - Ikeh, Michael E.i; Ifeanyieze, Florence O.; Ugwuoke, Cajethan Uche (Atmospheric and Climate Sciences, 2014)
The study was carried out to identify content areas of climate change for integration into the senior secondary school agricultural science curriculum in countries such as Nigeria. Two research questions were developed and answered by the study while two null hypotheses were formulated and tested. Descriptive survey research design was adopted for the study. The population for the study was 441 while the sample was 249. A 34-item structured questionnaire was developed for data collection. The questionnaire items were face-validated by five experts while Cronbach alpha method was used to determine the internal consistency of the items. The copies of the questionnaire were administered to the respondents with the help of two research assistants. Weighted mean was used to answer the research questions while t-test statistic was used to test the null hypotheses at 0.05 level of significance and 240 degrees of freedom. The findings of the study revealed that four clusters with 23 items were required for integration in the curriculum while 11 materials were identified to help teach the content areas. It was also found that there was no significant (p > 0.05) difference in the mean responses of Lecturers and extension agents on each item in the content areas of climate change and materials for teaching them. The study recommended among others that the clusters and 23 items with the materials identified by the study should be integrated into the agricultural science curriculum for teaching in secondary schools, especially in Nigeria.
Keywords: _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:sdg:13 Climate action; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found